Dichlorodifluoromethane-carbon dioxide: A dielectric mixture as a sustainable alternative to SF6 in high voltage applications - Khan, Sajjad Ali; Habib, Salman; Khan, Muhammad Yasir Ali; Chauhdary, Sohaib Tahir; Ali, Abdar; Kamel, Salah; Elnaggar, Mohamed F. (Frontiers in Materials, 2023)
Sulphur hexafluoride (SF6) gas is the frequently consumed gas in High Voltage (HV) applications due to its high dielectric and arch quenching property. However, due to its long Atmospheric Lifetime (AL), high Global Warming Potential (GWP), and other environmental concerns there is a need for a new sustainable gas as an alternative to SF6. Therefore, in this research, a dichloro-difluoromethane (R-12) in conjunction with carbon dioxide (CO2) is presented. Compared to SF6, R-12 has 99.65% shorter atmospheric lifetime and 89.78% less GWP. Moreover, CO2 is mixed with R-12 as a gas carrier to achieve a low boiling point as that of SF6. High Voltage Direct Current (HVDC), High Voltage Alternating Current (HVAC), and self-recoverability tests are conducted by under varying concentrations of gases ratios at different pressures and at standard constant temperature. Comparison analysis showed that R-12 dielectric strength is 0.9 times to SF6, and its mixture with CO2 possessed improved dielectric strength compare with nitrogen and air mixture beyond 30 lb/in2. For HVAC and HVDC, 50% of R-12 and CO2 mixture establishes an unim-peachable ratio for HV applications. The mixture has the self-recoverability property and pos-sesses positive synergism that give a conclusion that the mixture of R-12 with CO2 enhances the dielectric strength compared to pure gases and reduces the cost.